Multi-criteria decision analysis of waste-to-energy technologies for municipal solid waste management in Sultanate of Oman. Issue 7 (July 2018) - Qazi, Wajeeha A; Abushammala, Mohammed FM; Azam, Mohammed-Hasham
The Sultanate of Oman faces challenges, like rapid growth of waste generation, which calls for an optimum waste management strategy. Oman has witnessed the production of 1.5m t of municipal solid waste in 2012, which is expected to elevate to 1.89m t in 2030. This rapid increase needs to be tackled to reduce the generation rates along with the environmental impacts. Currently, there are no treatment facilities in Oman other than limited recycling, and therefore dumping waste into the landfill is the only ultimate way to dispose solid waste. Hence, this study is an initiative to improve the waste managing system in Oman by proposing optimum waste-to-energy technology using an analytical hierarchy process, manually and through expect choice software as well. In the present study, the identified important parameters were considered in an analytical hierarchy process model to rank the waste-to-energy technology alternatives. Based on the survey conducted, the most important criteria were environmental and economic, with the local priority vector of 0.400 and 0.277, respectively. This research concludes that the most suitable waste-to-energy technology for Oman, on the basis of the identified criteria, is anaerobic digestion followed by fermentation and incineration, which will help to reduce the amount of waste, greenhouse gas emissions and developing and maintaining costs of landfills.